Interactions between three typical endocrine-disrupting chemicals (EDCs) in binary mixtures exposure on myocardial differentiation of mouse embryonic stem cell. (July 2017) - Zhou, Ren; Cheng, Wei; Feng, Yan; Wei, Hongying; Liang, Fan; Wang, Yan
Abstract: In recent years, various kinds of endocrine-disrupting chemicals (EDCs) have been detected in human blood and urine. Thus, it was important to investigate the combined toxicity effect of EDCs. In the present study, we evaluated the individual and combined developmental toxicities of three classic EDCs: perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and bisphenol A (BPA) by embryonic stem cell test (EST). The similarities and differences between combination of same chemical group as well as different chemical groups were investigated in this research. Our results showed that the three compounds were all classified as weak embryotoxicity. The results of co-exposure revealed that there was synergistic action in combination of PFOS and BPA on myocardial differentiation. However, in all endpoints, the combined effects between PFOA with PFOS or BPA were both additive action. Therefore, we concluded that the additive effects were found in most different EDC mixtures whether they had similar structure or not. On the other hand, synergistic action was observed in a mixture of EDCs that belonged to a different chemical groups. Highlights: Binary mixtures of three EDCs mainly show additive effects on embryonic stem cell. Combination between BPA and PFOS shows synergistic actions on differentiation. Myh6 may be more efficient on combined toxicity evaluation than contract rate.